Proteomic Signatures of Monocytes in Hereditary Recurrent Fevers - Penco, Federica; Petretto, Andrea; Lavarello, Chiara; Papa, Riccardo; Bertoni, Arinna; Omenetti, Alessia; Gueli, Ilaria; Finetti, Martina; Caorsi, Roberta; Volpi, Stefano; Gattorno, Marco (Frontiers in Immunology, 2022)
Hereditary periodic fevers (HRF) are monogenic autoinflammatory diseases caused by mutations of MEFV, TNFRSF1A and MVK genes. Despite the identification of the causative genes, the intracellular implications related to each gene variant are still largely unknown. A large –scale proteomic analysis on monocytes of these patients is aimed to identify with an unbiased approach the mean proteins and molecular interaction networks involved in the pathogenesis of these conditions. Monocytes from HRF 15 patients (5 TRAPS, 5 FMF and 5 MKD) and 15 healthy donors were analyzed by liquid chromatography and tandem mass spectrometry before and after LPS stimulation. Significant proteins were analyzed through a Cytoscape analysis using the ClueGo app to identify molecular interaction networks. Protein networks for each HRF were performed through a STRING database analysis integrated with a DISEAES database query. About 5000 proteins for each HRF were identified. LPS treatment maximizes differences between up-regulated proteins in monocytes of HRF patients and HD, independently from the disease's activity and ongoing treatments. Proteins significantly modulated in monocytes of the different HRF allowed creating a disease-specific proteomic signatures and interactive protein network. Proteomic analysis is able to dissect the different intracellular pathways involved in the inflammatory response of circulating monocytes in HRF patients. Proteomics data may help to identify new possible unexplored intracellular pathways involved in HRF. These data can be used to find possible similarities between HRFs and multifactorial recurrent fevers (such as PAPA and SURF) and investigate proteins and pathways involved in their pathogenesis.